Valorização de resíduos agroindustriais por meio da recuperação de subprodutos em sistemas de digestão anaeróbia - Silva, Amanda de Sousa e (2020)
Carboxylic acids (CA), chemical-based compounds with several industrial applications, are conventionally produced through the petrochemical platform. However, due to environmental impacts, the risk of scarcity and high oil prices, organic production of CA from anaerobic digestion of low-cost renewable resources, such as organic waste, has received increasing attention. The general objective of the work was to evaluate the effect of different food/microorganism ratio (F/M) on the formation of bioproducts (carboxylic acids and alcohols) from residual glycerol, as well as to apply different mathematical models to the data of bioproducts formation and to select those that best describe the process. We also sought to analyze the potential of the biotechnological recovery of methane, hydrogen and carboxylic acids from agro-industrial wastewater (AWW) based on various data on the qualitative and quantitative composition of the AWW, as well as on the productivity found in several works in the literature regarding the formation of latter bioproducts. The Carboxylic Acid Production Potential (CAPP) assays were performed in batch reactors, in borosilicate, with a total volume of 300 mL. Four F/M ratios were tested, whose substrate content was varied and the inoculum concentration kept constant (2.5 gVSS L-1), obtaining ratios of 0.7; 1.1; 1.5; 2.1 gCOD gVSS-1. The residual glycerol showed a high potential for the production of carboxylic acids. After 28 days of fermentation in batch reactors fed with F/M ratios between 0.7-2.1 gCOD gVSS- 1, an average of 73-83% of the initial COD of the residual glycerol was converted into bioproducts, where the increase in the F/M ratio had a negative effect on the percentage of bioproducts conversion. There was also an influence on the profile of bioproducts. The acid formed in greater quantity for all the evaluated F/M ratios was HAc, which had its selectivity reduced from 84 to 73% with the increase in the F/M ratio. The production of HPr was more favored at F/M 1.5 and 1.3-PD at 2.1. In general, the maximum productivity of the bioproducts occurred during the first 7 days. The kinetic coefficients estimated by mathematical modeling of the organic matter conversions throughout the experiment suggest that the limiting step in the process is acidogenesis, possibly due to the low concentration of particulate material in the residual glycerol. The kinetic model that best fitted the hydrolysis and degradation curve of the substrate was the first order with residual. The studied AWWs showed to have excellent economic potentials for resource recovery, in which the CA platform seems to be more economically advantageous, especially when a chain elongation process is considered. However, the traditional anaerobic digestion is simpler in terms of process control and methane purification is usually easier and cheaper. Because of the low yields achieved, it seems that hydrogen production is the least attractive technological route. Therefore, it is necessary to analyze other factors such as the gross value-added, consolidation of the production and recovery techniques, the production scales and the possibility of installation in urban and rural environments to adopt the best choice of resource recovery platform.